The Walkways Landscape in Portugal: – Amieira Do Tejo Case-Study - Matos Rute Sousa; Azevedo António; Freire Francisco; Silva Luís (European Countryside)
Considering the concept of landscape as a vital experience, this paper seeks to ethically and aesthetically address walkways and their role in the landscape of inland Portugal. As such, the Amieira do Tejo walkway shall be employed as a case study, exploring the appropriation of these walkway by communities and tourists as well as the benefits they provide. The methodology used was based on bibliographic research and on the results of surveys and interviews carried out about the walkways. The data was quantitatively analysed in order to understand: the user’s perception of the quality of the landscape, the user’s perception of the impact of walkway on the landscape, and the benefits of the walkway to people’s quality of life. The results confirm the importance of the walkway to the landscape thanks to the extent to which they improve the quality of life of local inhabitants.